Specific features of anesthesia management in a patient with a transplanted heart - O. N. Yamshchikov; E. I. Zakurnaeva; A. P. Marchenko; S. A. Yemelyanov; M. A. Patronov; N. A. Marchenko (Трансплантология (Москва))
Background. The number of heart transplant patients makes 1 per 100,000 in the Russian Federation, 1.2 per 100,000 population in the Tambov Region. The medical community is poorly informed about the specific features of managing such patients during non-cardiac surgical interventions. The article presents a case report of the management of a patient with a transplanted heart undergoing surgery for acute appendicitis. Preoperative preparation, anesthesia management, surgery, and postoperative care and rehabilitation were provided taking into account the presence of a transplanted heart in the patient, according to the Guidelines developed by the experts of the V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs where the heart transplant had been performed to the patient, and standard clinical recommendations.Case Report. An 18-year-old patient diagnosed with acute phlegmonous appendicitis with a heart transplanted in 2021 for dilated cardiomyopathy underwent laparoscopic appendectomy 3 years after heart transplantation. Anesthesia was provided taking into account the presence of a denervated donor heart, a high risk of myocardial ischemia and heart ailure (low cardiac output syndrome), and the need for a timely correction of hypovolemia and hypotension. Anesthesia management was a general combined multicomponent anesthesia.Conclusion. This clinical case has shown the possibility of providing medical care to a patient with a transplanted heart at a modern level in an urban multidisciplinary hospital. Non-cardiac surgery was performed in accordance with recommendations of specialists of V.I. Shumakov Federal Research Center of Transplantology and Artificial Organs and clinical recommendations in order to achieve optimal results and the fastest possible rehabilitation in the postoperative period.